The Impact of Customer Satisfaction on Repurchase Intention (Surveys on Customer of Bloomythings) - Nurul Tufahati; Cecep Safa'atul Barkah; Pratami Wulan Tresna; Arianis Chan (Journal of Business & Applied Management, 2021)
This  study  seeks  to  determine  whether  customer  satisfaction  influences  repurchase  intentions  from Bloomythings'  customers  and  to  implement  strategies  to  increase  consumer  satisfaction  and  repurchase intention of Bloomythings. The resources obtained are then analyzed using quantitative research methods by conducting validity and reliability tests, normality tests, heteroscedasticity tests, and simple linear regression analysis  to  determine  the  effect  of  customer  satisfaction  on  repurchase  intention.  This  kind  of  survey  is  a survey supported by the distribution of questionnaires as a data collection tool. The samples in this study are customers from Bloomything who have  made purchases on Bloomythings products. The results showed that customer satisfaction had a positive and significant impact on repurchase intention.